2000
DOI: 10.1152/ajpcell.2000.279.1.c195
|View full text |Cite
|
Sign up to set email alerts
|

ROCK mediates thrombin's endothelial barrier dysfunction

Abstract: Thrombin-induced endothelial monolayer hyperpermeability is thought to result from increased F-actin stress fiber-related contractile tension, a process regulated by the small GTP-binding protein Rho. We tested whether this process was dependent on the Rho-associated protein kinase, ROCK, using a specific ROCK inhibitor, Y-27632. The effects of Y-27632 on thrombin-induced myosin light chain phosphorylation (MLCP) and tyrosine phosphorylation of p125 focal adhesion kinase (p125(FAK)) and paxillin were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
96
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 26 publications
10
96
1
1
Order By: Relevance
“…Therefore, inhibition of cell spreading as well as adhesion may account for the reduction of cell survival produced by disrupting the RhoA/ RhoA kinase pathway. Consistent with this notion, Y-27632 has been reported to block formation of stress fibers and cell spreading in various cell types including EC (21). In addition, Y-27632 inhibited phosphorylation of focal adhesion kinase and the assembly of focal contacts (21,26,48).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Therefore, inhibition of cell spreading as well as adhesion may account for the reduction of cell survival produced by disrupting the RhoA/ RhoA kinase pathway. Consistent with this notion, Y-27632 has been reported to block formation of stress fibers and cell spreading in various cell types including EC (21). In addition, Y-27632 inhibited phosphorylation of focal adhesion kinase and the assembly of focal contacts (21,26,48).…”
Section: Discussionsupporting
confidence: 56%
“…Consistent with this notion, Y-27632 has been reported to block formation of stress fibers and cell spreading in various cell types including EC (21). In addition, Y-27632 inhibited phosphorylation of focal adhesion kinase and the assembly of focal contacts (21,26,48). Moreover, activation of RhoA by CNF-1 increased the expression of focal adhesion kinase and promoted cell spreading (49).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…4d). In fact, transwell assay suggested that Y-27632 treatment actually enhanced endothelial barrier function by about twofold presumably via recruitment of F-actin to a-or bcatenin-containing junctions 20 . Interestingly, TiO 2 -NM treatment to Y-27632 preconditioned samples still led to an increase in dextran-FITC flux, albeit to a much lower level compared with the untreated Y-27632 control (Fig.…”
Section: Resultsmentioning
confidence: 99%